SOCIAL INCLUSION IN THE SCHOOL ENVIRONMENT THROUGH FOOTBALL: A LITERATURE REVIEW - dos Santos, Alisson Nonato; Santana, Ednaldo Correa (Seven Editora, 2026)
Football is a significant means of social inclusion within the sports context, especially for young people living in peripheral areas and urban centers. Cruz (2003) This article aimed to analyze school football as a tool for social inclusion. The methodology used was a Bibliographic Review, which according to Gil (2008) is a type of research based on the analysis of already published works, mainly scientific articles and books, with the objective of identifying the most relevant works for the research, examining the positions and conclusions of other authors. It was discussed how football, as a cultural phenomenon and a sport of great popularity, can contribute to the integration of students from different backgrounds, skills, and social contexts, promoting values such as respect, cooperation, and solidarity. Also addressed are the obstacles to inclusion, such as competitive culture, gender stereotypes, and structural limitations, in addition to proposals for more inclusive pedagogical practices.It is concluded that, with proper training, infrastructure, and ethical commitment, school football can be an important tool for building a more just, democratic, and inclusive school.